Paisagem Cultural de Transumância: A Rota da Serra da Estrela para as Campinas de Idanha - Carvalho, Raquel; Marques, Teresa Portela (CEM – Cultura, Espaço & Memória, 2021)
The transhumance cultural landscape reflects a deep knowledge of the territory. Based on pastoral activity, involves spatial, periodic and seasonal movements of livestock between mountain pastures, valleys and lowlands, to provide food. We highlight an important Portuguese route: Serra da Estrela – Idanha-a-Nova, where wool production was the main activity’s driving force. The activity reached its peak in the Middle Ages and survived until the 1950s in Beira Interior region. Aware that change is an inherent dynamic in landscape, we cannot, however, disregard that over generations, the use of endogenous natural resources, shows an understanding of the ecosystem, contributing to the region’s cultural and landscape identity heritage.